The development of a tool to promote sustainability in casting processes - Pagone, Emanuele; Jolly, Mark R.; Salonitis, Konstantinos (Elsevier, 2016)
The drive of the manufacturing industry towards productivity, quality and profitability has been supported in the last century by the availability of relatively cheap and abundant energy sources with limited focus on the minimisation of energy and material waste. However, in the last decades, more and more stringent regulations aimed at reducing pollution and consumption of resources have been introduced worldwide and in particular in Europe. Consequently, a highly mature and competitive industry like foundry is expecting challenges that an endeavour towards sustainability can turn into significant opportunities for the future. A tool to undertake a systematic analysis of energy and material flows in the casting process is being developed. An overview of the computer program architecture is presented and its output has been validated against real-world data collected from foundries.
Keywords: Energy efficiency; Sustainable development; Casting